Development and Standardization of a Peaceful Scoring Speed Test for Youth Basketball Players - Abbas, Ali Fadel (Pubmedia Jurnal Pendidikan Olahraga, 2025)
This study aimed to construct and standardize an objective test to measure the peaceful scoring speed of young basketball players in the 16 to 18 years old, determining the criteria of validity and reliability, and analyzing the differences between forwards and defenders. The research sample included 48 players from two local clubs, and an intensive six-week training programme was implemented using advanced measurement tools such as electronic watches and blood analysis devices. The results showed high validity and reliability for the test bar, with a consistency coefficient of 0.85 and a significant correlation with coaches' assessments of 0.78. It also recorded a statistically significant improvement in scoring time, which decreased from 43 seconds to 4. 15 seconds, and scoring accuracy increased from 65 to 75 after the programme, in addition to an average weight loss of 22 kilograms and an average fat percentage of 22 with high statistical significance. The attackers also outperformed the defenders in scoring speed and accuracy. The research recommends adopting the test in the periodic evaluation of players and designing customized training programmers based on its results, with the scope of the study expanded to include other age groups and genders. This study is a qualitative addition to the field of sports measurement, providing a reliable tool for improving the quality of training and building a standard database for future players.